2010
DOI: 10.1073/pnas.1002569107
|View full text |Cite|
|
Sign up to set email alerts
|

Improved IL-2 immunotherapy by selective stimulation of IL-2 receptors on lymphocytes and endothelial cells

Abstract: IL-2 immunotherapy is an attractive treatment option for certain metastatic cancers. However, administration of IL-2 to patients can lead, by ill-defined mechanisms, to toxic adverse effects including severe pulmonary edema. Here, we show that IL-2–induced pulmonary edema is caused by direct interaction of IL-2 with functional IL-2 receptors (IL-2R) on lung endothelial cells in vivo. Treatment of mice with high-dose IL-2 led to efficient expansion of effector immune cells expressing high levels of IL-2Rβγ, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
369
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(387 citation statements)
references
References 34 publications
15
369
0
3
Order By: Relevance
“…Subsequently, other reports described modified forms of IL2 that have attempted to favor ILRbg binding, prolong exposure, or mitigate toxicity. These include mutation of the IL2 amino acid sequence, fusion to a targeting antibody, or use of IL2/anti-IL2 antibody complexes (29)(30)(31). These alterations, like every new agent, need to be evaluated clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other reports described modified forms of IL2 that have attempted to favor ILRbg binding, prolong exposure, or mitigate toxicity. These include mutation of the IL2 amino acid sequence, fusion to a targeting antibody, or use of IL2/anti-IL2 antibody complexes (29)(30)(31). These alterations, like every new agent, need to be evaluated clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Ces anticorps, en recouvrant le site d'interaction de l'IL-2 avec la chaîne α de son récepteur, dirigent spécifiquement la cytokine vers le complexe dimérique. Les complexes anti-IL-2/IL-2 ainsi formés se révèlent avoir à faibles doses des activités anti-tumorales augmentées par rapport à des doses fortes d'IL-2, avec des effets secondaires très réduits [35]. Une stratégie alternative repose sur l'utilisation de l'IL-15 qui, comme l'IL-2, utilise les chaînes IL-2Rβ (CD122) et IL-2Rγ (CD132) du récepteur comme éléments de liaison et de transduction de signal.…”
Section: (➜)unclassified
“…The most common manifestation of IL-2 toxicity is capillary leak syndrome, resulting in a hypovolemic state and fluid accumulation in the extravascular space [13]. Krieg et al [7] discovered that VLS were mainly caused by IL-2Rabc non-immune cells activated by IL-2 in vivo. As IL-2-mediated VLS mainly depends on IL2Rabc ?…”
Section: Discussionmentioning
confidence: 99%
“…The main side effect was vascular leak syndrome (VLS) [5,6]. Krieg et al [7] found that the VLS was induced by interaction between IL-2 and IL-2Rabc. Thus, this experiment designed a new recombinant human IL-2 (rhIL-2) to block the binding of IL-2 and IL-2abc and to minimize the side effect of IL-2.…”
Section: Introductionmentioning
confidence: 99%